Development of experimental in vitro burn model - Fernandes,Ana Carolina Morais (2014)
PURPOSE: To propose an experimental burn model in NIH-3T3 cell line.METHODS:Induction of thermal injury in cultures of mouse fibroblast - NIH-3T3- cell line and determination of cell viability by MTT and imunofluorescence.RESULTS:The heating of the Petri dish increased proportionally to the temperature of the base and the time of exposure to microwave. In this in vitro burn model, using the cell line NIH-3T3 was observed drastic cellular injury with significant changes in cell viability and activity. It showed drastically modified cell morphology with altered membrane, cytoskeleton and nucleus, and low cellularity compared to the control group.CONCLUSION:The burn model in vitro using the cell line NIH-3T3 was reproductive and efficient. This burn model was possible to determine significant changes in cell activity and decreased viability, with drastic change in morphology, cell lysis and death.